Kontrola rezervoarjev za naftne derivate - Celin, Roman (Materiali in tehnologije, 2004)
The storage and handling of petroleum products requires that the products must have a minimum impact on the environment. New storage tanks are made witha double-shell, double-bottom, floating-membrane, dome roof and up-to-datemeasuring and regulation equipment. Despite all the regulations and safety measures, leaks or spills can occur, especially with older storage tanks. With regular inspections of the equipment, the shell, the foundations and the internals of the storage tanks, critical areas can be detected so as to minimise the possibility of leakage or spillage. In this presentation IMT's inspection experience of above-ground storage tanks is presented.
Keywords: rezervoarji; preiskava materialov; korozija